Graphenes prepared by Hummers, Staudenmaier and Hofmann methods for analysis of TNT-based nitroaromatic explosives in seawater - Ong, Beng Khong (2013)
The detection of TNT and related nitroaromatic compounds in seawater is of great interest. Electrochemical techniques can be applied for detection purposes since nitroaromatic compounds contain easily reducible nitro groups. In this study, we investigate the performance of thermally reduced graphenes prepared by three different oxidative methods: Hummers, Staudenmaier and Hofmann methods with consequent thermal exfoliation. The Hofmann method-based graphene was found to exhibit the highest sensitivity in detecting TNT electrochemically. Extended study on the detection of TNT in seawater using the graphene material provided significant improvements in the detection sensitivity. These findings will have profound impacts on the detection of nitroaromatic explosives in seawater.